Assessment of aquatic ecological health based on determination of biological community variability of fish and macroinvertebrates in the Weihe River Basin, China. (1st August 2020) - Wu, Jintao; Mao, Ruichen; Li, Mingyue; Xia, Jun; Song, Jingxi; Cheng, Dandong; Sun, Haotian
Abstract: A healthy aquatic ecosystem plays an important role in the operation of nature and the survival of human beings. Understanding the mechanism of its interaction with the habitat process is conducive to formulating targeted ecological recovery plans. In this study, fish and macroinvertebrates were collected from 49 investigation sites in the Weihe River basin, China, during periods of the summer and the autumn of 2017. Cluster analysis and canonical correlation analysis (CCA) were used to analyze the similarity of community distribution of fish and macroinvertebrates and their response to environmental variables. The biological integrity index of fish (F-IBI) and benthic-macroinvertebrate (B-IBI) was introduced to evaluate the aquatic ecological health. The results showed that fish communities were more coherent than macroinvertebrate communities. The distinguished response to ecological factors was identified for fish and macroinvertebrates. The ecological factors of total nitrogen, conductivity and river width have significant effects on both fish and macroinvertebrate communities. In addition, the fish community was significantly influenced by chlorine, fluorine, pH and flow velocity, while the macroinvertebrate community was significantly influenced by bicarbonate and water depth. The differences in community structure and response to ecological factors between communities were amplified in their environmental quality scores. Although F-IBI and B-IBI tend to be consistent temporally, the correlation is not significant. B-IBI showed decreasing gradient of ecological health status in the downstream area, while F-IBI tended to be different across river systems, which further illustrated the differences in the response of fish and macroinvertebrates to environmental variables. Highlights: The distribution of fish and macroinvertebrate community structures in the river basin were compared and analyzed. Fish and macroinvertebrates responded differently to ecological factors. Ecological features affecting fish and macroinvertebrate communities change seasonally. The spatial patterns of assessed aquatic ecological health based on fish and macroinvertebrates were demonstrated. The assessments of ecological health based on multiple biological communities is more reasonable and practical.